Structural energy storage composites for aviation applications - Chan, Kit-Ying; Demir, Baris; Lau, Kin-Tak; Shen, Xi (Frontiers in Aerospace Engineering, 2022)
Structural energy storage composites, which combine energy storage capability with load-carrying function, are receiving increasing attention for potential use in portable electronics, electric vehicles, and aircraft structures to store electrical energy in replace of traditional electrochemical energy storage devices. The integration of energy storage ability into mechanically strong carbon fibre reinforced polymer composite is promising in reducing the weight and volume while providing additional functions, ultimately leading to energy-efficient systems. In this review, the key designs and strategies to reconcile the trade-off between mechanical properties and energy storage performances of structural dielectric capacitors, a typical type of structural energy storage composites, are highlighted. Opportunities and challenges are also discussed for the further development of structural energy storage composites for aviation applications.